Multimodal Evaluation of Warmth Perception in Wood: An Experimental Study Based on Visual, Tactile, and Visual-Tactile Interactions - Yue Zhang; Wei Xiong; Yeyingzi Guo; Peixing Wei; Songlin Yi (BioResources, 2025)
The inherent warmth of wood is widely valued in design applications, yet the mechanisms underlying its perception across different sensory modalities have not been fully explored. The aim of this work was to investigate the physical properties that influence warmth perception of wood across different species and surface treatments, and to clarify the respective contributions of visual and tactile warmth during multisensory integration. In this work, 10 material samples were technically characterized and their perceived warmth was evaluated by participants under three conditions: vision-only, touch-only, or combined visual-tactile interactions. Infrared thermography was used to quantify material temperature changes. Results showed that color dominated warmth perception under the visual assessment, while thermal properties and hand-material interface temperature differences significantly influenced tactile warmth perception. Wood species exhibited substantial effects on warmth perception, whereas surface treatments showed limited impact. Visual-tactile warmth perception was significantly positively correlated with both modalities, predominantly mediated by tactile inputs during direct contact, with visual characteristics providing critical complementary information. These findings advance the understanding of wood’s multisensory warmth perception and provide valuable insights for user-centered wood space and product design.